From Data to Delight: Leveraging Social Customer Relationship Management to Elevate Customer Satisfaction and Market Effectiveness - Ibrahim A. Elshaer; Alaa M. S. Azazz; Sameh Fayyad; Shaimaa A. Mohamed; Amr Mohamed Fouad; Eslam Ahmed Fathy (Information)
The current study aims to investigate ways through which the data on social customer relationship management (SCRM) enhance customer satisfaction (CS) as well as market effectiveness (ME) in the hotel industry. Moreover, it examines the mediator role of customer involvement using social media data (CIUSM). The moderating role of customer information processing capability (CIPC) between social customer relationship management (SCRM) and customer involvement using social media (CIUSM) was examined. Therefore, following the suggestions from Dominant (S-D) Logic, Social Exchange Theory (SET), and Dynamic Capabilities Theory (DCT), this research explores the role of SCRM in co-creation and organizational performance through the social media data of customers. Using PLS-SEM through SmartPLS, data from 389 participants were analyzed. The findings proved that SCRM directly improves both customer satisfaction and the effectiveness of the market due to the indirect effect of CIUSM data as a mediator among them. Also, it showed that SCRM improves directly CIUSM. Moreover, it proved the direct effect of CIUSM on customer satisfaction and market effectiveness. Moreover, CIPC, as a moderator, enhances SCRM impacts by demonstrating how hotels leverage data from social media activity as a competitive advantage. Based on the findings of this study, the three integrated theories provide a single framework to delve deeply into the intricate association between social media customer involvement to enhance hotel performance. Also, it ensures that hospitality managers engage customers, continuously respond to their needs and requirements, and embrace efficient data processing to deploy SCRM effectively.